Analisis Dampak Perkembangan Pasar Pancur Batu terhadap Transformasi Sosial-Ekonomi Masyarakat Sekitar, 1960-2023 - Lubis, Nadiyah Zahra; Nugraha, Muhammad Adika; Nababan, Surya Aymanda (Medan Resource Center, 2024)
This study explores the history and socio-economic impact of Pancur Batu Market from 1960 to 2022, focusing on trader activities and community effects. Employing a qualitative case study approach, data were collected through observations, interviews, and document analysis. The findings reveal that Pancur Batu Market has evolved significantly from a colonial-era facility into a pivotal economic and social hub for the local community. Officially inaugurated in the 1970s, the market facilitates the sale of basic necessities and serves as a platform for social interaction. Trading activity intensifies on Saturdays, attracting crowds that cause congestion and lead some traders to operate exclusively on these days. The market plays a vital role in community life, fostering social harmony and providing a primary livelihood source for many residents. Economically, it generates business opportunities and improves living standards. Despite challenges such as competition and price fluctuations, Pancur Batu Market remains a cornerstone of the community's socio-economic landscape.